La forêt en Ceinture verte d’Île-de-France : un patrimoine paysager métropolitain à la flore peu diversifiée - Fabien Roussel (Bulletin de l’Association de Géographes Français, 2019)
The green belt of the Île-de-France region is situated 10 to 30 km around the city of Paris. Forest cover represents a quarter of its total area. This forest cover is mostly composed of large public forests – Montmorency, Sénart, Notre-Dame or Saint-Germain – managed by the Forest National Office. Those forests have kept their land cover against the urban sprawl since the 18th century as the Cassini map shows. In the context of growing environmental expectations from city dwellers and public authorities at a metropolitan scale (the Greater Paris region), it becomes relevant to direct attention to their plant diversity.This article is based on landscape and botanical analysis of the public forests of Montmorency and Chevreuse Valley compared to small, isolated, private, sometimes abandoned woods from the surrounding areas. In city dwellers’ minds, forest remains an ideal place to experience “nature”, as shown by the series of surveys we made in Montmorency forest. However, the most frequented forests habitats offer low plant diversity compared to the small isolated woods. In the green belt forests, landscape is the main heritage driver.